Perancangan Prototype Alat Keamanan Menggunakan Face Unlock Berbasis Website (Studi Kasus: Prima Unggul) - Diva Randy Baskara; Sofyan Mufti Prasetiyo (CV. Shofanah Media Berkah, 2025)
This research aims to design and build a prototype room security system using website-based face unlock technology as a solution to improve security in the SMK Prima Unggul environment. This system uses facial recognition technology integrated with an ESP32-CAM device and a Python-based website. The development method used is the prototype method, starting from design, manufacture, to system testing using the black box testing method. The implementation results show that the system can accurately recognize registered users' faces, unlock doors automatically using a solenoid door lock, and record access data in real time via the website. This system has proven effective in improving room security and can be further developed with notification features or live video surveillance.